That "Vaulty Night": Trials, Testimonies, and Critiques of Justice in Beckett's Panopticon Prison-stage. (February 2022) - Diver, Alice
Beckettian justice avoids the usual scripts of judicial processes: his trials and punishments merge, as his captive characters lock themselves into eerily repetitive, self-questioning loops of semi-existence. His prison-cell courtrooms critique the wider socio-cultural symbolism associated with indefinite incarceration and unduly harsh sentences, questioning whether retributive sanctions have the power to redeem, or to spark atonement. By turning vague but terrifying recollections into accusatory witness statements, Beckett crafts purgatories grounded in endless perception. Audiences must therefore act as jurors and gaolers: by witnessing the various "crimes" of omission (neglect, abandonment, unintentional cruelty) we are perhaps better placed to judge our own failings and frailties and capacity for resilience.